1972
DOI: 10.1152/ajplegacy.1972.223.1.194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estradiol on sodium and potassium balances in adrenalectomized dogs

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1976
1976
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Ele vated All levels produce an opposite effect. Since estrogens exert a mineralocorticoid effect in addition to their effect on the renin-aldosterone system [21] it might be argued that in this study a positive sodium balance may be responsible for the observed dowm-regulation of the adrenal All recep tor via lowered circulating All (table III, All at 14 days). This does not appear to be the predominant mechanism of action since up-regulation of the mesenteric artery All re ceptor was not observed at any time period during the pres ent study.…”
Section: Discussionmentioning
confidence: 65%
“…Ele vated All levels produce an opposite effect. Since estrogens exert a mineralocorticoid effect in addition to their effect on the renin-aldosterone system [21] it might be argued that in this study a positive sodium balance may be responsible for the observed dowm-regulation of the adrenal All recep tor via lowered circulating All (table III, All at 14 days). This does not appear to be the predominant mechanism of action since up-regulation of the mesenteric artery All re ceptor was not observed at any time period during the pres ent study.…”
Section: Discussionmentioning
confidence: 65%
“…Estrogen usage induced many physiological changes including alterations of vascular reactivity [Rosenfeld and Jackson, 1984;Naden and Rosenfeld, 1985;Vargas et al, 1995], sympathetic activity [Iversen, 1973] and the sodium balance [Johnson et al, 1972]. Specific binding sites of estrogen have been reported in aorta and cardiac ventricular tissues of both male and female rats [Stumpf et al, 1977;Lin and Shain, 1985].…”
mentioning
confidence: 99%
“…All these changes were accompanied by an increase in weight in 4/6 sub¬ jects, with a return to normal of all the parameters within 4 days of cessation of oestrogen administra¬ tion. Oestrogens produce sodium and water reten¬ tion in animals even during the phase of sodium escape to mineralocorticoid (Johnson et al 1970) or in adrenalectomized animals (Johnson et al 1972) but not in hypophysectomized animals sug¬ gesting that the water retention at least was me¬ diated by vasopressin release, as has been observed in rats (Skowski et al 1979). The exact mechanism by which oestrogens modify the response of AVP release to an osmolar stimulus remains unclear.…”
Section: Discussionmentioning
confidence: 74%